3D shape-from-shading relies on a light source prior that does not change with age. (December 2020) - Pickard-Jones, Beverley; d'Avossa, Giovanni; Sapir, Ayelet
Abstract: The light-from-above prior enables observers to infer an object's three-dimensional shape-from-shading information. Young, Western adults implicitly assume the light source is placed not only above, but also to the left of, the observer. Previous evidence reached conflicting conclusions regarding the development of the assumed light source direction. In the present study, we measured the light source prior cross-sectionally in children aged 5–11 years, using an explicit shape judgement task. The light-from-above prior, and the left bias, were present as soon as children became sensitive to shading information, regardless of their age. Global processing preference was not related to the ability to perform the task. Similarly, scanning habits, as measured by reading proficiency and starting position in a cancellation task, were not related to the magnitude of the left bias. Children's ability to report shape-from-shading judgements increased with age, but age did not affect the direction of light priors. Thus, we concluded that the development of the light-from-above prior and leftward bias do not require an extended maturation period, but rather the direction of the light-source priors may be developmentally stable once measurable.